3-2(1-8x)=4(6x+2)-7

Simple and best practice solution for 3-2(1-8x)=4(6x+2)-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3-2(1-8x)=4(6x+2)-7 equation:


Simplifying
3 + -2(1 + -8x) = 4(6x + 2) + -7
3 + (1 * -2 + -8x * -2) = 4(6x + 2) + -7
3 + (-2 + 16x) = 4(6x + 2) + -7

Combine like terms: 3 + -2 = 1
1 + 16x = 4(6x + 2) + -7

Reorder the terms:
1 + 16x = 4(2 + 6x) + -7
1 + 16x = (2 * 4 + 6x * 4) + -7
1 + 16x = (8 + 24x) + -7

Reorder the terms:
1 + 16x = 8 + -7 + 24x

Combine like terms: 8 + -7 = 1
1 + 16x = 1 + 24x

Add '-1' to each side of the equation.
1 + -1 + 16x = 1 + -1 + 24x

Combine like terms: 1 + -1 = 0
0 + 16x = 1 + -1 + 24x
16x = 1 + -1 + 24x

Combine like terms: 1 + -1 = 0
16x = 0 + 24x
16x = 24x

Solving
16x = 24x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-24x' to each side of the equation.
16x + -24x = 24x + -24x

Combine like terms: 16x + -24x = -8x
-8x = 24x + -24x

Combine like terms: 24x + -24x = 0
-8x = 0

Divide each side by '-8'.
x = 0

Simplifying
x = 0

See similar equations:

| 5x-2b=4 | | 7x+3b=23 | | x^2=342-x | | 5=5(x-2)-(x-7) | | 9x+9+11+11x=180 | | p-3(n-5)=30 | | 2-4-3x=3-4 | | 8e(-e)=10 | | x^2-2mx+m^2-m+1=0 | | -7+7x=-x-8(-2-x) | | 16x^2+64x-48=0 | | Log(9)(X)=1/2 | | ((24x^2)-2c-11)=0 | | Log(32)(X)=1/5 | | (24x^2c-11)=0 | | 5x/24=39 | | F=B(1+rt) | | 7s=5 | | 3x^2+xy-2y^2=o | | 3p^2-pq-2q^2=0 | | 4=3G | | 3x+35=8 | | 3(6x-5)+15x= | | F(x)=x^3-7x^2+24x-18 | | 2*x+0.5x+0.25x+1=100 | | F(x)=x^3+24x^2+7x-18 | | 584000= | | 3n^4-6n^2+9n=0 | | (1)4x+2=5 | | Y=-1x-(4) | | (3x+5)*2x=25 | | x-10=180 |

Equations solver categories